The effects of football practice on children's fundamental movement skills: A systematic review and meta-analysis - Mao, Xiaojin; Zhang, Jingyue; Li, Yulian; Cao, Yuang; Ding, Meng; Li, Weidong; Fan, Lixia (Frontiers in Pediatrics, 2022)
The purpose of this systematic review and meta-analysis was to explore the effects of different football practices on fundamental movement skills (FMS) of children of different ages and genders, in order to help children to improve their FMS through football practice more effectively. The databases of CNKI, Wanfang database, Pubmed, Web of science and Cochrane library were searched and the quality of the included studies was evaluated by using the Cochrane Risk of Bias Tool, and Meta-analysis was conducted by Review Manager 5.4 software. A total of 16 studies involving 3121 subjects aged 7-13 years were eventually included. The results showed that football had a positive effect on linear sprint ability (SMD 95%CI＝-0.37 [-0.61, -0.14]，P＝0.002), horizontal jump(SMD 95%CI＝0.22 [-0.34, 0.77],P＝0.003), object control (SMD 95%CI＝1.32 [0.8, 1.85], P＝0.0003), Closed-eye single-leg test (SMD 95%CI＝0.87[0.48,1.25], P＜0.0001),while countermovement jump(SMD 95%CI＝0.50[-0.35,1.35], P＝0.25) and flamingo balance (SMD 95%CI＝-0.16[-0.31,-0.02]，P＝0.03) has no facilitating effect. Meanwhile, subgroup analyses were performed, linear sprint running has a significant facilitation effect in the 1200-2399min, 7-9 years, male and female subgroups(P＜0.05), horizontal jumping was significantly facilitated in the ≥3600min, 7-9 years, male subgroup(P＜0.05), closed-eye single-leg test was significantly facilitated in the 7-9 years, 10-13 years, male and female subgroups(P＜0.05), the effect of the duration of the intervention on balance remains to be studied. The present meta-analysis indicates that football practices promote FMS in children, and the impact of different football practices contents and other sports on children's FMS could be further explored in the future, to enrich the training methods of FMS in order to promote children's motor development more effectively.